Polyethylene Glycol-Modified Poly(Styrene-co-Ethylene/Butylene-co-Styrene)/Carbon Nanotubes Composite for Humidity Sensing - Mičušík, Matej; Chatzimanolis, Christos; Tabačiarová, Jana; Kollár, Jozef; Kyritsis, Apostolos; Pissis, Polycarpos; Pionteck, Jürgen; Vegso, Karol; Siffalovic, Peter; Majkova, Eva; Omastová, Mária (Frontiers in Materials, 2019)
Polymeric composites of linear triblock copolymer poly(styrene-co- ethylene/butylene-co-styrene) with a maleic anhydride unit (SEBS-MA) modified by hydrophilic polyethylene glycol (PEG) with various amounts of conducting filler - carbon nanotubes (CNT) - were prepared by solvent casting. The CNT surface was modified by a noncovalent approach with a pyrene-based surfactant to achieve a homogeneous dispersion of the conducting filler within the polymeric matrix. The dispersion of the unmodified and surfactant-modified CNT within the elastomeric SEBS-MA and SEBS-MA-PEG matrices was characterized by studying the morphology (SEM, TEM). A dynamical mechanical analysis was used to evaluate the interaction between the CNT and copolymer matrix. The electrical conductivity of the prepared composites was measured by dielectric relaxation spectroscopy, and the percolation threshold was calculated. The prepared elastomeric composites were characterized and studied as humidity sensor. Our results demonstrated that an MWCNT concentration slightly above the percolation threshold could result in large signal changes. In our system, good results were obtained for an MWCNT loading of 2 wt. % and an 0.1 mm thin composite film. The thickness of the tested elastomeric composites and the source current appear to be very important factors that influence the sensing performance.